2022
DOI: 10.5624/isd.20210244
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of normal condyles and those with disc displacement with reduction in the Indonesian population: A CBCT study

Abstract: Purpose Disc displacement can cause resorption of the head of the condyle and affect its volume. This study analysed the volume of normal condyles and those with disc displacement with reduction (DDR) in cone-beam computed tomography (CBCT) scans from the Indonesian population. Materials and Methods This study analysed 56 condyles (26 normal and 30 with DDR) from patients who visited the Oral and Maxillofacial Radiology Unit after being referred from the Prosthodontics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although there was a poor correlation between condylar changes (as observed on CBCT images), pain, and symptoms in TMJ OA [ 30 ]. Many studies have confirmed the correlation between condylar bone changes and articular disc displacement and believed that it is related to TMD symptoms [ 31 , 32 ]. Consistent with previous research results, normal condylar morphology was 75.1% in the asymptomatic group and 48.9% in the symptomatic group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a poor correlation between condylar changes (as observed on CBCT images), pain, and symptoms in TMJ OA [ 30 ]. Many studies have confirmed the correlation between condylar bone changes and articular disc displacement and believed that it is related to TMD symptoms [ 31 , 32 ]. Consistent with previous research results, normal condylar morphology was 75.1% in the asymptomatic group and 48.9% in the symptomatic group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D measurement started from condylar image segmentation and reconstruction based on previous studies. 42 , 43 The superior contour of the condyle was determined as the first radiopaque point found in the upper articular area. The lowest point of the sigmoid notch is the marker point of the bottom of the condyle.…”
Section: Methodsmentioning
confidence: 99%